Daughter centrioles assemble preferentially towards the nuclear envelope in Drosophila syncytial embryos. - Cunningham, N.H.J.; Bouhlel, I.B.; Conduit, P.T. (Open biology, 2022)
Centrosomes are important organizers of microtubules within animal cells. They comprise a pair of centrioles surrounded by the pericentriolar material, which nucleates and organizes the microtubules. To maintain centrosome numbers, centrioles must duplicate once and only once per cell cycle. During S-phase, a single new 'daughter' centriole is built orthogonally on one side of each radially symmetric 'mother' centriole. Mis-regulation of duplication can result in the simultaneous formation of multiple daughter centrioles around a single mother centriole, leading to centrosome amplification, a hallmark of cancer. It remains unclear how a single duplication site is established. It also remains unknown whether this site is pre-defined or randomly positioned around the mother centriole. Here, we show that within Drosophila syncytial embryos daughter centrioles preferentially assemble on the side of the mother facing the nuclear envelope, to which the centrosomes are closely attached. This positional preference is established early during duplication and remains stable throughout daughter centriole assembly, but is lost in centrosomes forced to lose their connection to the nuclear envelope. This shows that non-centrosomal cues influence centriole duplication and raises the possibility that these external cues could help establish a single duplication site.